Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/pharmaceutics15030782
|View full text |Cite
|
Sign up to set email alerts
|

Virus-like Particle Vaccine Expressing the Respiratory Syncytial Virus Pre-Fusion and G Proteins Confers Protection against RSV Challenge Infection

Abstract: Respiratory syncytial virus (RSV) causes severe lower respiratory tract disease in children and the elderly. However, there are no effective antiviral drugs or licensed vaccines available for RSV infection. Here, RSV virus-like particle (VLP) vaccines expressing Pre-F, G, or Pre-F and G proteins on the surface of influenza virus matrix protein 1 (M1) were produced using the baculovirus expression system, and their protective efficacy was evaluated in mice. The morphology and successful assembly of VLPs were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Although we previously showed that N is not required for VLP assembly [ 18 ], we opted to include N because humans mount a significant humoral and cellular response to N, and N is increasingly recognized as a virulence factor [ 21 , 22 , 23 , 24 , 25 , 27 , 29 , 65 ]. Whereas several studies show that G and F antigens are ultimately better when combined in one vaccine [ 15 , 87 ], this study served to test our approach and GCR antigen design and its ability to raise protective Abs. In contrast to most other subunit approaches, we applied our VLPs IN because the initial site of infection is a factor in the induction of tissue-resident memory cells and because of the mounting evidence for the importance of local mucosal immunity in reducing RSV infection and disease severity in animals and humans [ 29 , 68 , 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we previously showed that N is not required for VLP assembly [ 18 ], we opted to include N because humans mount a significant humoral and cellular response to N, and N is increasingly recognized as a virulence factor [ 21 , 22 , 23 , 24 , 25 , 27 , 29 , 65 ]. Whereas several studies show that G and F antigens are ultimately better when combined in one vaccine [ 15 , 87 ], this study served to test our approach and GCR antigen design and its ability to raise protective Abs. In contrast to most other subunit approaches, we applied our VLPs IN because the initial site of infection is a factor in the induction of tissue-resident memory cells and because of the mounting evidence for the importance of local mucosal immunity in reducing RSV infection and disease severity in animals and humans [ 29 , 68 , 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that G protein is not necessary for enhanced disease to occur [ 88 ], and G does not always induce enhanced disease [ 15 , 16 , 17 , 85 ]. In our case, VLP-GCR induced very low levels of anti-G Abs, and challenge of vaccinated animals with wt RSV displayed weight losses that exceeded the post-challenge weight losses observed in mock-vaccinated mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VLPs were characterized via transmission electron microscopy and Western blot following the methods previously described. 11 Briefly, VLPs stained with 2% uranyl acetate were observed using the Bio-High voltage EM system (JEM-1400 Plus at 120kV and JEM-1000BEF at 1000kV, JEOL Ltd., Tokyo, Japan) and checked for proper assembly. For Western blot analysis, VLPs were separated using 10% sodium dodecyl sulfate polyacrylamide gels.…”
Section: Characterization Of the Vlpsmentioning
confidence: 99%
“…Initially, VLP assembly using entirely authentic RSV protein components was disregarded due to inefficient virion particle assembly resulting in low yields. 8 This led to the formation of heterologous VLPs using the protein components derived from the Newcastle disease virus, influenza virus, and others, [9][10][11] as the process of RSV VLP assembly was poorly understood at the time. Later studies did reveal that the RSV F, M, N, and P proteins are the minimum requirements for proper particle assembly, with phenylalanine residue in the F protein cytoplasmic tail and the M protein being integral for virion assembly.…”
Section: Introductionmentioning
confidence: 99%